(untitled) (Journal Of Educational and Psychological Researches, 2014)
For over a decade, educational technology has been used sparingly in our schools and universities. Online training courses have been used since 2003 to fill the gaps in our learning system and to add extra program besides classroom learning. This paper aims to investigate the Iraqi EFL instructors’ participating in online training courses and its influence on the process of teaching and learning. The sample of present study consists of 30 instructors from University of Baghdad. The questionnaire of sixteen items was constructed. After ensuring validity and reliability of questionnaire, it was applied on March 2013 and the result shows that most of instructors improve their teaching methods by participating in online training courses and they prefer E-learning to enrich their experience in English language teaching. In the light of the findings of the present study, relevant conclusions and recommendations are put forward.